2022
DOI: 10.3390/ijms232314581
|View full text |Cite
|
Sign up to set email alerts
|

DeepHP: A New Gastric Mucosa Histopathology Dataset for Helicobacter pylori Infection Diagnosis

Abstract: Emerging deep learning-based applications in precision medicine include computational histopathological analysis. However, there is a lack of the required training image datasets to generate classification and detection models. This phenomenon occurs mainly due to human factors that make it difficult to obtain well-annotated data. The present study provides a curated public collection of histopathological images (DeepHP) and a convolutional neural network model for diagnosing gastritis. Images from gastric bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Additionally, the diagnosis accuracy of endoscopists using LCI images is consistent with this [16]. Brazilian scholars Gonçalves et al [17] believe that CNN models can detect HP infection and inflammation spectrum in gastric mucosal tissue pathology biopsies, and they provide the DeepHP database. A study on digital pathology (DP) found that virtual slide images obtained by scanning Warthin-Starry (W-S) silver-stained tissues with a 20× resolution scanner can reliably identify HP, with an F1 score of 0.829 for the AI classifier [18].…”
Section: Hp Infectionsupporting
confidence: 70%
“…Additionally, the diagnosis accuracy of endoscopists using LCI images is consistent with this [16]. Brazilian scholars Gonçalves et al [17] believe that CNN models can detect HP infection and inflammation spectrum in gastric mucosal tissue pathology biopsies, and they provide the DeepHP database. A study on digital pathology (DP) found that virtual slide images obtained by scanning Warthin-Starry (W-S) silver-stained tissues with a 20× resolution scanner can reliably identify HP, with an F1 score of 0.829 for the AI classifier [18].…”
Section: Hp Infectionsupporting
confidence: 70%